Hypersensitive pneumonitis and cardiovascular comorbidity - A. V. Medvedev; N. G. Demyanenko; G. E. Alichubanova; S. A. Kasimtseva; M. N. Kovalevskaya; R. V. Tarasov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Relevance. The incidence of hypersensitivity pneumonitis (HSP) is 1.64–2.21 cases per 100,000 population per year. The combination of HSP and cardiovascular diseases (CVD) leads to mutual aggravation of the course of pathologies, changes in the clinical picture and worsening of the prognosis. Accumulation of knowledge about the mechanisms of mutual influence of HSP and CVD is important for optimization of treatment and diagnostic approaches. Objective: to study the factors influencing the prognosis of hypersensitivity pneumonitis in patients associated with cardiovascular diseases.Object and methods. A retrospective analysis of the database of 228 patients with HSP was performed. The main group consisted of 152 patients with HSP in combination with CVD, the comparison group - 76 patients without CVD. In the main group, the following subgroups were identified: with arterial hypertension (55 people), with ischemic heart disease (40 people), with atrial fibrillation (34 people) and with chronic heart failure (23 people). A comprehensive analysis of clinical symptoms, spirography results, diffusing capacity of the lungs (DLCO), computed tomography, echocardiography, vascular stiffness indices and the severity of comorbidity according to the Charlson index was performed.Results. The Charlson index indices were significantly higher in patients with HPP and CVD (from 2.3 to 6.9 points in different subgroups) compared to the group without CVD (1.02 points). All patients showed a statistically significant correlation of the Charlson index with age, systolic pressure in the pulmonary artery, fibrosis area according to the Warrick scale, FVC indices and diffusing capacity of the lungs. In patients with CVD, additional predictors of an increase in the Charlson index were vascular stiffness parameters (aortic pulse wave velocity, reflected wave propagation time) and structural heart parameters (thickness of the posterior wall and interventricular septum of the left ventricle, left ventricular myocardial mass). The most pronounced mutual aggravation was found in the subgroup of patients with HPP and chronic heart failure.Conclusion. The combination of hypersensitivity pneumonitis with cardiovascular diseases significantly aggravates the course of both pathologies. Early detection of risk factors and assessment of concomitant conditions using the Charlson index allows optimizing the diagnosis and treatment of this category of patients. Particular attention should be paid to older patients with signs of pulmonary hypertension, fibrotic changes in the lungs and decreased diffusion capacity of the lungs.